Inventari de la sagristia de la Seu de Manresa (1452) - Masnou i Pratdesaba, Josep M. (Miscel·lània litúrgica catalana, 2007)
The oldest inventory of the sacristy of the Cathedral of Manresa dates from 1452. The publication of this interesting text shows all pieces of goldsmith?s art, the frontal and sacred ornaments as well as the liturgical books the Augustinian canons kept for celebrating the divine cult, some of which offered specifically for the liturgical cult of the holy bodies of St. Fructuosus, St. Maurice and St. Agnes.